A Review on the Bioinspired Photocatalysts and Photocatalytic Systems. (3rd March 2022) - Yang, Liuqing; Fan, Deqi; Li, Zhaolin; Cheng, Yelan; Yang, Xiaofei; Zhang, Tierui
Abstract: After long‐term evolution, organisms in nature have achieved optimal structure, organization, and function to adapt to the environment. Some ingenious biological structures have highly efficient solar light absorption, matter transmission, and natural photocatalytic properties, such as leaves, sunflowers, seaweeds, algae, bacteria. Artificial photocatalysis, which involves CO2 reduction and water splitting to obtain green renewable energy or oxygen, is of great significance for solving the problem of energy shortages, achieving carbon neutrality, and building a sustainable society. In order to improve the efficiency of artificial photocatalysis, it is necessary to develop highly efficient photocatalysts by expanding ideas and drawing innovative inspiration from nature. Artificially constructed photocatalysts with bionic structures achieved by simulating natural organisms have gradually become an exciting research field with great potential in recent years. This article reviews bioinspired photocatalysts and photocatalytic systems from the aspects of principle, composition, construction method, and the achieved performance. It is expected that this review will help researchers develop a systematic and in‐depth understanding for the biomimetic design of photocatalysts and photocatalytic systems. Abstract : By imitating the microstructure of photosynthetic organisms to obtain a photocatalyst, or following the macroengineering principles of nature for generating a photocatalytic system, artificial photocatalysis can be improved. This review aims to analyze the relevant research progress and help researchers establish a systematic and in‐depth understanding of bionic design for photocatalysts and photocatalytic systems.